2012
DOI: 10.1177/1753944712464102
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation following autologous stem cell transplantation in patients with multiple myeloma: incidence and risk factors

Abstract: AF is very frequent in patients with multiple myeloma when they receive ASCT. The presence of abnormal renal function, left ventricular systolic dysfunction, dilated left atrium, or hypertension at baseline identifies patients at high risk of developing AF following ASCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Due to recent treatment advances, patients with multiple myeloma (MM) are living longer (Anderson, 2012;Kumar et al, 2014;Liwing et al, 2014), underscoring the importance of patient quality of life and management of adverse events (AEs) related to therapy. MM patients are at risk of cardiac events due to age and disease-related factors (McBride et al, 1988;Inanir et al, 1998;Robin et al, 2008;Kistler et al, 2012;Kwaan, 2013); there is also a risk of cardiac events due to cardiotoxicity from treatments including anthracyclines (Ky et al, 2013), proteasome inhibitors (Bockorny et al, 2012;Lonial et al, 2012;Herndon et al, 2013;Honton et al, 2013;Siegel et al, 2013) and high-dose therapy (Fatema et al, 2009;Chow et al, 2011;Sureddi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to recent treatment advances, patients with multiple myeloma (MM) are living longer (Anderson, 2012;Kumar et al, 2014;Liwing et al, 2014), underscoring the importance of patient quality of life and management of adverse events (AEs) related to therapy. MM patients are at risk of cardiac events due to age and disease-related factors (McBride et al, 1988;Inanir et al, 1998;Robin et al, 2008;Kistler et al, 2012;Kwaan, 2013); there is also a risk of cardiac events due to cardiotoxicity from treatments including anthracyclines (Ky et al, 2013), proteasome inhibitors (Bockorny et al, 2012;Lonial et al, 2012;Herndon et al, 2013;Honton et al, 2013;Siegel et al, 2013) and high-dose therapy (Fatema et al, 2009;Chow et al, 2011;Sureddi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Furthermore, malignancy-associated anemia can further provoke arrhythmias via cardiac ischemia or high-output heart failure. 20,34 Regarding transplant-associated risks, Benjamin et al conducted a study that demonstrated an increase in the incidence of AF in HSCT patients in spite of the same risk factors in the general population. 35 Hence, this outcome might give a clue that the disease itself or factor related to hematopoietic stem cell transplantation would essentially impact the occurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 13 cohort studies consisting of 10 587 HSCT patients were enrolled. 1,3,7,[17][18][19][20][21][22][23][24][25][26] The literature retrieval, review, and selection process are demonstrated in Figure 1. The characteristics of the included studies are presented in Table 1.…”
Section: Re Sultmentioning
confidence: 99%
“…There were no differences in arrhythmia incidence between patients receiving myeloablative or reduced or nonmyeloablative chemotherapy, but patients undergoing allogeneic HSCT were more likely to experience arrhythmia than patients receiving autologous transplant, also more likely was arrhythmia when patients were treated with ATG (Tonorezos et al., ). Moreover, Singla, Hidalgo and other authors identified the following risk factors for arrhythmias after HSCT: the older age, presence of premature supraventricular complexes or atrio‐ventricular conduction delay (1st or 2nd degree atrioventricular block) during pretransplant period, history of prior arrhythmia, presence of valvular abnormality, increased atrial size in echocardiography, history of hypertension and/or coronary artery disease, being on beta blocker treatment or the other antiarrhythmic agent and prior anthracycline use anthracycline dose of >400 mg/m 2 , lower ejection fraction of the left ventricle at baseline examination in echocardiography, baseline renal dysfunction (Hidalgo et al., ; Peres et al., ; Singla et al., ; Sureddi et al., ). Fatema declared a phenomenon of weight gain of or equal to 7% accompanied by and presence of diastolic dysfunction at diagnosis in patients with multiple myeloma is also a risk factor, which is not surprising as for cardiologist weight gain is one of the marker of ongoing progression of heart failure (Fatema et al., ).…”
Section: Discussionmentioning
confidence: 99%